2020
DOI: 10.1186/s12913-020-05239-w
|View full text |Cite
|
Sign up to set email alerts
|

Violence and aggression in psychiatric inpatient care in Sweden: a critical incident technique analysis of staff descriptions

Abstract: Background: Violence towards staff working in psychiatric inpatient care is a serious problem. The aim of the present study was to explore staff perspectives of serious violent incidents involving psychiatric inpatients through the following research questions: Which factors contributed to violent incidents, according to staff? How do staff describe their actions and experiences during and after violent incidents? Methods: We collected data via a questionnaire with open-ended questions, and captured 283 incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 52 publications
5
40
0
2
Order By: Relevance
“…Victims of physical aggression-leaving aside physical damage-can report a vast array of psychological consequences, whose seriousness ranges from adjustment symptoms up to posttraumatic stress disorders [123•, 124]. Verbal aggression has been found to produce angst, depression, and other emotional distress, with repercussions on morale, professional replacement, quality of care, and patient recovery processes [125][126][127].…”
Section: Discussionmentioning
confidence: 99%
“…Victims of physical aggression-leaving aside physical damage-can report a vast array of psychological consequences, whose seriousness ranges from adjustment symptoms up to posttraumatic stress disorders [123•, 124]. Verbal aggression has been found to produce angst, depression, and other emotional distress, with repercussions on morale, professional replacement, quality of care, and patient recovery processes [125][126][127].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of violence management at youth inpatient facilities in a Nordic context have concluded that a supportive team of staff members who share common beliefs is vital (Pelto-Piri et al, 2017), as are preventive approaches (Pelto-Piri et al, 2020). First, external factors (organizational, situational, and relational) are significant causes of violence and may be easier to modify than internal youth factors.…”
Section: Introductionmentioning
confidence: 99%
“…Second, improving staff competence in the use of deescalation techniques is essential. Third, management should regularly follow up with staff after violent incidents and increase psychological support (Pelto-Piri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The particular vulnerability for trauma in staff working within forensic DD services represents a major clinical concern. For staff, research has documented adverse impacts on work functioning and burnout (Oates et al, 2020), levels of anxiety and depression (d' Ettore and Pellicani, 2017), perceptions of safety (Pelto-Piri et al, 2020) and physical health (Kelly et al, 2016). Such adversities may also translate into consequences for service users, resulting in poorer quality of care (Arnetz and Arnetz, 2001) and a longer length of stay in services (Broderick et al, 2015).…”
mentioning
confidence: 99%
“…There is substantial evidence demonstrating the benefits of work-based counselling, for both the individual affected and the organisation within which they work (Greenwood, 2006), preventing the worsening of psychopathological symptoms and improving work functioning (Klaver et al, 2020). Yet, whilst the need for personal and emotional support for staff working in such settings is recognised in clinical guidance (National Institute for Health and Care Excellence, 2015), the actual provision of post-incident support within forensic and health-care settings is less documented (Pelto-Piri et al, 2020), and self-care behaviours to combat work-related stress are not frequently practiced by staff (Keesler and Troxel, 2020). Therefore, insight into the levels of access to trauma support for staff working in DD settings and the associated outcomes for this particularly at-risk group is key.…”
mentioning
confidence: 99%